Synthesis, characterization and thermal behaviour of solid 2- methoxycinnamylidenepyruvate of some bivalent metal ions in CO2 and N2 atmospheres - De Carvalho, C. T.; Siqueira, A. B.; Ionashiro, E. Y.; Ionashiro, M. [UNESP] (Ecletica Quimica, 2010)
Solid State M-2-MeO-CP compounds, where M stands for bivalent metals (Mn, Fe, Co, Ni, Cu and Zn) and 2-MeO-CP is 2-methoxycinnamylidenepyruvate, were synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), elemental analysis and complexometry were used to establish the stoichiometry and to study the thermal behaviour of these compounds in CO and N atmospheres. The results were consistent with the general formula: M(L)2·H2O. In both atmospheres (CO2, N2) the thermal decomposition occurs in consecutive steps which are characteristic of each compound. For CO2atmosphere the final residues were: Mn3O4, Fe3O4, Co3O4, NiO, Cu2O and ZnO, while under N2atmosphere the thermal decomposition is still observed at 1000° C.
Keywords: 2-methoxycinnamylidenepyruvate; Bivalent metals; CO2N2; Thermal behaviour